PROPERTIES OF SOME NEW SEMINORMED SEQUENCE SPACES DEFINED BY A MODULUS FUNCTION - Altin, Yavuz; Gokhan, Aysegul; Altinok, Hifsi (Univ Babes-Bolyai, 2005)
In this paper we introduce the sequence spaces (c) over cap (0)(p,f,q,s),(c) over cap (p,f,q,s) and (m) over cap (p, f ,q ,s) using a modulus function f and defined over a seminormed space (X ,q) seminormed by q. We study some properties of these sequence spaces and obtain some inclusion relations.
Keywords: Modulus function; seminorm; almost convergence; sequence spaces